Gout: why is this curable disease so seldom cured?. Issue 11 (3rd August 2012) - Doherty, Michael; Jansen, Tim L; Nuki, George; Pascual, Eliseo; Perez-Ruiz, Fernando; Punzi, Leonardo; So, Alexander K; Bardin, Thomas
Abstract : Gout is the most common inflammatory arthritis and one in which pathogenesis and risk factors are best understood. One of the treatment objectives in current guidelines is 'cure'. However, audits show that only a minority of patients with gout receive adequate advice and treatment. Suboptimal care and outcomes reflect inappropriately negative perceptions of the disease, both in patients and providers. Historically, gout has been portrayed as a benign and even comical condition that is self-inflicted through overeating and alcohol excess. Doctors often focus on managing acute attacks rather than viewing gout as a chronic progressive crystal deposition disease. Urate-lowering treatment is underprescribed and often underdosed. Appropriate education of patients and doctors, catalysed by recent introduction of new urate-lowering treatments after many years with no drug development in the field, may help to overcome these barriers and improve management of this easily diagnosed and curable form of potentially severe arthritis.